A simulation of integrated gasification, energy generation, and GIS from solid waste in Jazan Municipalities, KSA (Part 1: Gasification) - Mohamed Hassan; Salih Eltahir Elmarud Ali; Mahmoud Abdelrahim Abdelgiom (Ain Shams Engineering Journal)
This paper aims to use GIS software to choose the energy plant’s ideal location based on side selection criteria and to build a simulation using Aspen Plus software to estimate the gas production. The outcome of this spatial analysis using GIS will typically encompass a prioritized list of potential sites, accompanied by visual maps that illustrate suitable locations, constraints, and accessibility. The simulation was validated using experimental and simulation data from the literature on plasma gasification. The results of this study showed good matching with the literature data. After the simulation was validated, it was used to study the case of Jazan region MSW. The results showed that the gas composition is 12.93 % H2, 8.68 % CO2, 3.08 % N2, 0.08 % H2S, and 31.11 % CO, with a temperature of 1210 °C. This gas was transferred to energy production simulation to generate energy, which will be discussed in part 2 of this paper.